Low Grade Appendiceal Mucinous Neoplasms- A Short Case Series with Review of Literature - Salapathi, S; Rajeshwari, B; Niamath, Sadiya; Ghosh, Mitra (Annals of Pathology and Laboratory Medicine, 2021)
Low-grade appendiceal mucinous neoplasm (LAMN) is a rare malignancy and is found in less than 0.3% of appendectomy specimens. Patients with LAMN can present with abdominal pain and mimic clinically as appendicitis, intussusception or obstruction, hence high clinical suspicion is needed for correct diagnosis and management. The exact nature and nomenclature of these tumors when they disseminate into the peritoneum is controversial. The prognosis of LAMN is highly dependent on the presence or absence of neoplastic epithelium outside the appendix. Tumors with extra appendiceal acellular mucin in the right lower quadrant only rarely recur but tumors with extra appendiceal mucin and neoplastic epithelium recur more often. LAMNs with diffuse peritoneal seeding of neoplastic epithelium and mucin have a progressive clinical course that frequently results in death of the patient. Hence whenever a case of mucinous neoplasm of the appendix is encountered, it is essential that the entire appendix be submitted for histopathologic examination and should be thoroughly evaluated for presence of extra appendiceal mucin and neoplastic epithelium, and also for the type of invasion in order to obtain the correct diagnosis and to predict the risk of recurrence. We present here three cases of low grade appendiceal tumors with their varied clinical presentation and histopathological findings, for their rarity and clinical importance.